Electrophysical properties of thin films of indium oxide - Volobuev, Vlas S.; Dolgiy, Valeriy K.; Pochtenny, Artyom E. (Journal of the Belarusian State University. Physics, 2023)
The electrophysical properties of thin films of indium oxide have been researched. The structure and chemical composition of the films were studied by electron diffraction, scanning electron microscopy and X-ray photoelectron spectroscopy. The temperature dependence of the conductivity of these films was measured at a constant oxygen concentration by cyclic thermal desorption. It is shown that the interaction of adsorbed particles with the film leads to the formation of various adsorption states that affect the electrophysical properties of the film. Based on the results of the study, a mechanism of conduction is proposed. The increase in conductivity associated with a decrease in the concentration of adsorbed oxygen is due to the fact that adsorbed oxygen is the centers of scattering of charge carriers, and a decrease in its concentration leads to an increase in the mobility of charge carriers. The results can be used in microelectronic sensors and sensors, since they have a higher response speed and significantly less reading drift compared to resistive sensors.
Keywords: sensors; conduction mechanism; thin film; hopping conductivity; thermal desorption